Conceptualising the liberal ideal: the discursive construction of education in the promotion of international development 2000 – 2020 - Wash, Ian (2022)
This thesis advances our understanding of the ideational drivers behind international education policy of the new millennium by taking an interpretive approach to the key policy documents. Discourse analysis is used to examine the main policy reports produced by the most influential bodies in this field, notably the World Bank and UN agencies, between 2000 and 2020. It finds that international education policy was discursively constructed as a grand narrative about the vision, process and outcomes of education in the promotion of international development. Yet the thesis argues that the dominant liberal model informing policy practices in this field was compromised by an overly simplistic one-size-fits-all approach to constructing the challenges and finding solutions in international education. To be specific, the analysis finds that the international policy realm was dominated by thinking grounded in economic liberalism.